2022
DOI: 10.3389/fmed.2022.934270
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune and immunoserological markers of COVID-19 pneumonia: Can they help in the assessment of disease severity

Abstract: BackgroundImmune dysregulation and associated inefficient anti-viral immunity during Coronavirus Disease 2019 (COVID-19) can cause tissue and organ damage which shares many similarities with pathogenetic processes in systemic autoimmune diseases. In this study, we investigate wide range autoimmune and immunoserological markers in hospitalized patients with COVID-19.MethodsStudy included 51 patients with confirmed Severe Acute Respiratory Syndrome Coronavirus 2 infection and hospitalized due to COVID-19 pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
1
Order By: Relevance
“…Anticuerpos antinucleares en COVID-19 parte, los desenlaces informados asociados con la positividad de ANA también mostraron heterogeneidad. Mientras que algunos estudios establecieron una relación entre la positividad de ANA y los desenlaces adversos, como mortalidad, ingreso en la unidad de cuidados intensivos, estancias hospitalarias más largas y duración de la ventilación mecánica, otros no lograron establecer tales asociaciones [27][28][29][30] . Sorprendentemente, algunos estudios informaron incluso una relación positiva entre la presencia de ANA y mejores desenlaces clínicos, en especial en términos de parámetros de laboratorio asociados con una intensa actividad del sistema inmunitario y un estado protrombótico 17,27 .…”
Section: Discussionunclassified
“…Anticuerpos antinucleares en COVID-19 parte, los desenlaces informados asociados con la positividad de ANA también mostraron heterogeneidad. Mientras que algunos estudios establecieron una relación entre la positividad de ANA y los desenlaces adversos, como mortalidad, ingreso en la unidad de cuidados intensivos, estancias hospitalarias más largas y duración de la ventilación mecánica, otros no lograron establecer tales asociaciones [27][28][29][30] . Sorprendentemente, algunos estudios informaron incluso una relación positiva entre la presencia de ANA y mejores desenlaces clínicos, en especial en términos de parámetros de laboratorio asociados con una intensa actividad del sistema inmunitario y un estado protrombótico 17,27 .…”
Section: Discussionunclassified
“…Similar to patients infected with other viruses, infected with SARS-CoV-2 show altered autoantibody profiles (Zhou Y. et al, 2020;Peker et al, 2021;Scappaticcio et al, 2021b), such as, antinuclear antibodies, antithyroid antibodies, chromatin proteins, ribosomal proteins, and immunerelated proteins (Bastard et al, 2020;Chang et al, 2021;Ulndreaj et al, 2022). These autoantibodies are closely correlated with the disease severity and the prognosis of COVID-19 patients and may trigger long-COVID-19 symptoms (Pascolini et al, 2021;Stjepanovic et al, 2022;Son et al, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that COVID-19 is related to autoimmune diseases, based on traditional biochemical and molecular markers [ 16 ]. Patients with pre-existing inflammatory or autoimmune conditions, such as cancer, obesity, hypertension, cardiovascular disease, type 2 diabetes, or connective tissue disorders, are at a higher risk of fatal outcomes if autoantibodies are present.…”
Section: Introductionmentioning
confidence: 99%